(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Field experimental was carried out at Kalabsho - El-Dakhlia Governorate, Egypt, Â in 2013/14 and 2014/2015 winter growing seasons.Â To study effect of last regime irrigation before harvest by 15 and 30 days and spacing hills 15, 20 and 25 cm between plants in addition to three cultivars (Sultan, Farida and Samba) on sugar beet yield and quality under reclaimed soils in Kalabsho location. Split-Split plot design were used in both season. Main plots allocated with regime irrigation befor harvest, sub-plots were take with hill spacing between plants whearas, cultivars were arranged in sub-sub plots. Main results were obtained can summarized as folllow: Wih decreasing the gap between last irrigation and harvest to 15 days caused to gave significant increase in value of top fresh weight and root yields, this was true in both seasons (0.361and 0.283 kg/plant) and (25.59 and 26.00 ton/fed.) respectivety. On the other direction,with increasing the gab between last irrigation and harvest untill 30 days resulting in significant differences among mean values of root fresh weight kg/plant,sugar yield ton/fed.,sucrose %,total soluble solids and purity percentages in both seasons. These trends due to,with elonation the period before harvest with out water supply reduced water content in roots through 30 days compared to 15 days befor harvest which was notenough to exhibited any enjourity to plants, or decreasing in water root content. Planting sugar beet seeds at 20 cm. between hills progressive than other distance (15 and 25 cm.) for most important characters,root,top fresh weight, sucrose and purity %. On the other hand space 15 cm. between hills gave the highest values of top fresh weight,root yield, sugar yield and sucrose % in the first season.Â Cultivar,Farida gave the highest values of root fresh weight,root yields,sugar yields,sucroseÂ % and T.ss % in the first season and purity in the second season. Significant interaction effects were found between main three factors under study illustrated that spacing hill 20 cm. between plants,preventation irrigation befor harvest by 30 days with used Farida cultivare gave the highest values for most important characters under study.